CHINA’S OUTWARD FOREIGN DIRECT INVESTMENT IN THE AGRICULTURAL SECTOR: TRENDS AND PROSPECTS - DU, Wei; LISHCHYNSKYY, Ihor (Journal of European Economy, 2024)
China leads the world in the volume of outward foreign direct investment (FDI) in agriculture. This status is the result of long-term policies, including the agricultural «going out» strategy and the «Belt and Road» initiative. Despite this leadership, the overall volume of both total FDI and agricultural FDI has been declining in recent years. This paper aims to analyse the structure and trends of Chinese outward FDI in agriculture, given the limited availability of statistical data. The results show that the total volume of China’s agricultural FDI exceeded $106.98 billion (7.4% of China’s total outward FDIs) in the period from 2005 to 2023. Despite fluctuations in investment volume, there has been a growth trend, with a peak in 2017 marked by significant transactions such as the acquisition of Syngenta. Developed countries are the primary recipients of Chinese FDI in agriculture, while developing countries dominate Chinese construction projects. The list of both investors and builders includes predominantly state-owned enter prises. In summary, the trajectory of Chinese outward foreign direct investment in agriculture presents a compelling narrative of strategic global engagement and economic expansion. JEL: F21, Q17.